Peranan Motivasi Kerja Pada Kinerja Pegawai di Kantor Desa Peniraman Kabupaten Mempawah - Yuni Firayanti; Fidia Wulan Sari; Rini, Rini (Jurnal Multidisiplin Indonesia, 2024)
This study aims to determine the role of work motivation in employee performance at the Pemiraman Village Office, Mempawah Regency. The research method used is a qualitative research method, which is a research method based on the philosophy of postpositivism, used to research on the condition of natural objects. This research was carried out at the Pemiraman Village Office of Mempawah Regency by selecting 7 informants who were considered representative of their respective employees, namely 1 village head as a key informant and 6 employees as employees who also played an important role. The data collection techniques used in this study are in-depth interviews, observation and documentation. The results of the study show that work motivation plays a very important role for employees to support their performance. And the performance of employees of the Mempawah Regency Village Office can be said to be very good, which can be seen from the creation of job satisfaction as employees and can improve the welfare of the village office.